Potential of Exoskeleton Technologies to Enhance Safety, Health, and Performance in Construction: Industry Perspectives and Future Research Directions. Issue 3 (2nd October 2019) - Kim, Sunwook; Moore, Albert; Srinivasan, Divya; Akanmu, Abiola; Barr, Alan; Harris-Adamson, Carisa; Rempel, David M.; Nussbaum, Maury A.
OCCUPATIONAL APPLICATIONS: Work-related musculoskeletal injuries and disorders remain an important problem in the construction industry. Exoskeletons are an emerging wearable technology that assists or augments a user's physical activity or capacity. This technology is a potential solution to reduce the physical demands and fatigue experienced by construction workers and help improve worker safety, health, and performance. As a first step towards enabling exoskeleton use in construction, we captured the perspectives of construction industry stakeholders regarding adopting exoskeletons and continued use in practice. Stakeholder responses highlighted several important questions and concerns, which were grouped using qualitative content analysis into three categories: (1) expected benefits, (2) exoskeleton technology adoption factors, and (3) perceived barriers to use. Uncertainties were expressed about the practical value and usability of exoskeleton technologies, and the impact of this technology on worker safety. Given this, and the limited state of current evidence, we summarize important research gaps that need to be addressed in future for successful adoption and use of exoskeleton technologies in the construction industry.